The sum of us : how racism hurts everyone : adapted for young readers - McGhee, Heather, 1980- (2023)
"This book, edited for young readers, is a call to action. McGhee examines how damaging racism is not only to people of color but also to white people. She offers hope and real solutions so that we can all prosper. An expert in economic policy, Heath McGhee draws lessons from her work running a think tank and her travels around the country talking to everyday Americans who are coming together to fight for a more just and inclusive society. The people she meets prove how much the stories we tell ourselves about race and belonging influence the policies that determine our shared economic future."--
An old story : the zero-sum hierarchy -- Racism drained the pool -- Going without -- Ignoring the canary -- No one fights alone -- Never a real democracy -- Living apart -- The same sky -- The hidden wound -- The solitary dividend.
"This book is based on The Sum of Us: What Racism Costs Everyone and How We Can Prosper Together, copyright ©2021 by Heath McGhee, Published in hardcover in the United States by One World, an imprint of Random House, a division of Penguin Random House LLC, in 2021."--Title page verso.
Includes index.
Ages 10 and up.
Keywords: Racism -- United States -- Juvenile literature; Racism; Race relations -- Economic aspects; Racism; United States -- Race relations -- Economic aspects -- Juvenile literature; United States; Young adult literature; Juvenile works